Villas, sanctuaries and settlement in the Romano-British countryside : new perspectives and controversies - Henig, Martin,; Soffe, Grahame,; Adcock, Kate,; King, Anthony, (Archaeopress Roman archaeology ;, 2023)
This volume brings together a range of papers on buildings that have been categorised as 'villas', mainly in Roman Britain, from the Isle of Wight to Shropshire. It comprises the first such survey for almost half a century.